Heparin-induced thrombocytopenia in a cardiac surgery patient with early and persistent thrombocytopenia and initial negative immunological and functional assays. Issue 169 (September 2018) - Patel, Rima; Varga, Cindy
Highlights: HIT can be a challenging diagnosis in cardiac surgery patients. Case of early and persistent post-operative thrombocytopenia Initial immunologic and serologic HIT assays negative but ultimately had HIT Important to weigh clinical suspicion with laboratory results when diagnosing HIT